2022
DOI: 10.1186/s12912-022-00895-1
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ knowledge and understanding of obstacles encountered them when administering resuscitation medications: a cross-sectional study from Palestine

Abstract: Background Medication errors (ME) are one of the most important reasons for patient morbidity and mortality, but insufficient drug knowledge among nurses is considered a major factor in drug administration errors. Furthermore, the complex and stressful systems surrounding resuscitation events increase nursing errors. Aims This study aimed to assess the knowledge about resuscitation medications and understand the obstacles faced by nurses when givin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(74 reference statements)
0
0
0
Order By: Relevance
“…The result of this study found that more than fifty percent (55.3%) of nurses had adequate level of knowledge regarding administration of drugs during CPR which was similar to study done in Palestine found that 58.6% nurses had knowledge on resuscitation medication 12 , similarly 56.5% nurses had knowledge on high-alert medications. 6 This finding was quite low compared to different studies found that70.5% in Taiwan 5 , 60.9% 13 and 75.8% in Palestine 2 and also demonstrated that nurses are insufficient information about high alert medications and resuscitation medications in Palestine.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The result of this study found that more than fifty percent (55.3%) of nurses had adequate level of knowledge regarding administration of drugs during CPR which was similar to study done in Palestine found that 58.6% nurses had knowledge on resuscitation medication 12 , similarly 56.5% nurses had knowledge on high-alert medications. 6 This finding was quite low compared to different studies found that70.5% in Taiwan 5 , 60.9% 13 and 75.8% in Palestine 2 and also demonstrated that nurses are insufficient information about high alert medications and resuscitation medications in Palestine.…”
Section: Discussionsupporting
confidence: 79%
“…This finding is inconsistent with the study conducted in Palestine but age, education level, CPR training, working experience, and hospital were not significant association with knowledge. 12 However, several studies demonstrated that a significant relation between total working experience and the knowledge score 5,6,13 , professional qualification and the knowledge score 2 , and also between the CPR training and the knowledge score on high-alert medications. 5 These difference findings might be due to study setting, varies in working experiences, differences in professional qualification and duration of training.…”
Section: Discussionmentioning
confidence: 99%